2010
DOI: 10.2337/db10-0174
|View full text |Cite
|
Sign up to set email alerts
|

Increased Reactive Oxygen Species Production and Lower Abundance of Complex I Subunits and Carnitine Palmitoyltransferase 1B Protein Despite Normal Mitochondrial Respiration in Insulin-Resistant Human Skeletal Muscle

Abstract: OBJECTIVEThe contribution of mitochondrial dysfunction to skeletal muscle insulin resistance remains elusive. Comparative proteomics are being applied to generate new hypotheses in human biology and were applied here to isolated mitochondria to identify novel changes in mitochondrial protein abundance present in insulin-resistant muscle.RESEARCH DESIGN AND METHODSMitochondria were isolated from vastus lateralis muscle from lean and insulin-sensitive individuals and from obese and insulin-resistant individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
130
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(151 citation statements)
references
References 52 publications
16
130
0
Order By: Relevance
“…The current study, however, demonstrated that acute peak physiological fatty acid elevation does not impair mitochondrial enzyme activities or ATP production, which can instead be enhanced by higher lipid substrate availability even in the presence of enhanced ROS production. While this last finding is consistent with a recent study showing that high ROS production in ageing human skeletal muscle is not associated with impaired mitochondrial respiration [27], the current results support the view that the onset of insulin resistance is, at least in part, independent of the inhibition of mitochondrial enzyme activities and ATP production capacity [27].…”
Section: Discussionsupporting
confidence: 93%
“…The current study, however, demonstrated that acute peak physiological fatty acid elevation does not impair mitochondrial enzyme activities or ATP production, which can instead be enhanced by higher lipid substrate availability even in the presence of enhanced ROS production. While this last finding is consistent with a recent study showing that high ROS production in ageing human skeletal muscle is not associated with impaired mitochondrial respiration [27], the current results support the view that the onset of insulin resistance is, at least in part, independent of the inhibition of mitochondrial enzyme activities and ATP production capacity [27].…”
Section: Discussionsupporting
confidence: 93%
“…Skeletal muscle mitochondria 233:1 from type 2 diabetes patients exhibited lower activity of the respiratory chain (Kelley et al 2002, Ritov et al 2010, most probably arising from a reduction in the expression of genes encoding mitochondrial enzyme subunits (Mootha et al 2003, Patti et al 2003. Heilbronn and coworkers (Heilbronn et al 2007) and Lefort and coworkers (Lefort et al 2010) found a decrease in several markers of mitochondrial metabolism in IR subjects. Similar results were also obtained in overweight children (Fleischman et al 2009) and in patients with genetic defects in insulin receptor signaling (Sleigh et al 2011).…”
Section: Mitochondrial Dysfunction In Insulin Resistancementioning
confidence: 99%
“…Several studies have shown that skeletal muscle mitochondrial ROS production is increased in insulinresistant conditions [1,2], which are an early hallmark in the development of type 2 diabetes. Moreover, it has been suggested that ROS and oxidative stress are causal factors of skeletal muscle insulin resistance [3,4].…”
Section: Introductionmentioning
confidence: 99%